Insights into psychosocial problems and associated factors among higher education students in Ethiopia: a cross-sectional study - Hailay Tesfay Gebremariam; Million Desalegn Tassew; Frehiwot Sahle Woldemaryam (BMC, 2024)
Abstract While there has been extensive research on well-known psychosocial problems like depression, anxiety, and stress among higher education students, emerging issues such as emotional problems, antisocial behavior, trauma experiences, and academic difficulties are not as thoroughly studied, particularly in the context of Ethiopian higher education students. These updated psychosocial problems are crucial to explore due to their potentially significant impact on students' academic performance, personal development, and future prospects. Therefore, this study aims to explore the current psychosocial issues faced by adolescent students at Arba Minch University and identify the factors associated with them. To accomplish this objective, a survey questionnaire was distributed to a sample of 300 university students through a cross-sectional study. The survey questionnaire was designed to provide a thorough understanding of the various types of psychosocial problems experienced by the students. The findings revealed that the most prevalent psychosocial problems among higher education adolescent students were emotional problems (6.7% high/severe, 46.3% moderate), antisocial behavior (5% high/severe, 54.7% moderate), trauma experiences (7% high/severe, 23% moderate), and academic problems (8.3% high/severe, 23% moderate). The prevalence of no/low psychosocial problems was 47%, 40.3%, 69.3%, and 68.7%, respectively. Additionally, statistically significant (p < 0.05) associated factors to these psychosocial problems were identified: gender for academic problems, religion affiliation for antisocial behavior, trauma experiences, marital status for trauma experiences, living situation during holidays for emotional problems, age for emotional problems and antisocial behavior, and educational sponsorship for antisocial behavior. The study found that students who lacked a support system, such as family or friends, were more likely to experience psychosocial problems. In conclusion, psychosocial problems among adolescent students in higher education are a pressing issue that requires immediate attention. By understanding the challenges faced by these students, universities can implement effective interventions to support their mental well-being.